Behring Sea Award Act, 1894 [electronic resource] : [57 Vict. Ch. 2]. - Great Britain. Behring Sea Award Act, 1894. ([S.l.] : Printed by Eyre and Spottiswoode, for T.D. Pigott, 1894)
Cover title. "Arrangement of sections. Section. I. Enactment of articles of arbitrators' award respecting the fur seal ." "An Act to provide for carrying into effect the Award of the Tribunal of Arbitration constituted under a Treaty between Her Majesty the Queen and the United States of America"--p. 1. "A.D. 1894." Electronic reproduction. Mode of access: Internet. 44